(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Histopathology, crucial for disease diagnosis, heavily relies on effective tissue fixation to maintain cellular architecture. However, the carcinogenic nature of formalin has spurred interest in safer alternatives. Moringa oleifera, renowned for its medicinal properties, presents a promising natural fixative candidate. This study aimed to assess Moringa oleifera extract’s viability as a fixative for histopathological applications, specifically focusing on its compatibility with subsequent histological analyses. Distilled water and normal saline solutions of Moringa extract were prepared at varying concentrations. Kidney tissue samples from euthanized rats were treated with these solutions alongside formalin. Tissue sections underwent manual processing, embedding, sectioning, and staining using Hematoxylin and Eosin (H&E) technique. Microscopic examination revealed varying degrees of tissue preservation across Moringa concentrations and solvents. Higher concentrations (15%) in distilled water exhibited optimal preservation, akin to formalin-fixed tissues, while lower concentrations and normal saline solutions showed suboptimal fixation. These findings highlight Moringa oleifera’s potential as a tissue fixative, particularly at higher concentrations in distilled water. Further research is recommended to isolate active components and explore alternative Moringa extracts for enhanced tissue preservation. Comparative studies would elucidate the efficacy of Moringa-derived fixatives and inform their utilization in histopathological practice.